The Role of Internal Audit in Encouraging Good University Governance: A Study on Private Universities - Anggraini, Leriza Desitama; Ghina, Aliah; Faradillah (Universitas Indo Global Mandiri, 2025)
The demand for accountability and transparency in higher education governance highlights the strategic role of internal audit in strengthening institutional management, particularly in private universities. This study aims to examine the effect of internal audit effectiveness on the accountability and transparency of private universities in Palembang. A quantitative approach with an explanatory survey was applied, involving 10 private universities with active internal audit units. Primary data were collected from 50 respondents using a 5-point Likert-scale questionnaire and analyzed through linear regression using RapidMiner Studio. The findings reveal that both internal indicators (IN) and accountability activities (KA) have a positive influence on achieving good university governance (GUG), with the regression model Y = 0.336 × IN + 0.387 × KA + 1.244. The KA variable has a slightly greater impact than IN, although both are statistically significant. The Root Mean Squared Error (RMSE) value of 0.170 indicates a very low prediction error and high model accuracy. These results imply that strengthening both accountability mechanisms and internal audit practices simultaneously is essential to support accountable and transparent university governance. Keywords: internal audit, accountability, transparency, linear regression, good university governance